Some room for us: Women in academia as seen through the lives of Canada’s Eliza Ritchie (1856-1933) and Spain’s María Goyri (1873-1954) - Sara Herrero; Allyson Jule (Historia y Comunicación Social, 2021)
This paper explores the experience of women in academia by looking both back and at the present. We consider two women who searched for and found academic accomplishment. Together, they serve as representatives of a new way of living for women in the late-19th and early-20th centuries. Eliza Ritchie (1856-1933) from Canada and María Goyri (1873-1954) from Spain are exemplars of the emerging contributions of women in the academy as part of the changing role for women in Western culture and the need for women to support each other in shared feminist causes. These women shared the same time period, the same intellectual values, the same commitment to scholarship, and the same incredible determination to help develop a modern society that could embrace the full incorporation of women. This paper considers their accomplishments in light of academia today in both Canada and Spain in regards to the advancement of women. It also examines some lingering inequalities in terms of tenure and promotion, salary, research capacity, administrative and leadership positions. Such an international collaboration contributes to the shared sense of sisterhood for women in academia today.